Advances in Atmospheric Radiation Measurements and Modeling Needed to Improve Air Safety. Issue 4 (10th April 2015) - Tobiska, W. Kent; Atwell, William; Beck, Peter; Benton, Eric; Copeland, Kyle; Dyer, Clive; Gersey, Brad; Getley, Ian; Hands, Alex; Holland, Michael; Hong, Sunhak; Hwang, Junga; et al.
Abstract Air safety is tied to the phenomenon of ionizing radiation from space weather, primarily from galactic cosmic rays but also from solar energetic particles. A global framework for addressing radiation issues in this environment has been constructed, but more must be done at international and national levels. Health consequences from atmospheric radiation exposure are likely to exist. In addition, severe solar radiation events may cause economic consequences in the international aviation community due to exposure limits being reached by some crew members. Impacts from a radiation environment upon avionics from high‐energy particles and low‐energy, thermalized neutrons are now recognized as an area of active interest. A broad community recognizes that there are a number of mitigation paths that can be taken relative to the human tissue and avionics exposure risks. These include developing active monitoring and measurement programs as well as improving scientific modeling capabilities that can eventually be turned into operations. A number of roadblocks to risk mitigation still exist, such as effective pilot training programs as well as monitoring, measuring, and regulatory measures. An active international effort toward observing the weather of atmospheric radiation must occur to make progress in mitigating radiation exposure risks. Stakeholders in this process include standard‐making bodies, scientific organizations, regulatory organizations, air traffic management systems, aircraft owners and operators, pilots and crew, and even the public.